Análise térmica computacional via CFD OpenFOAM - Moura, Vitor Furtado de (2018)
The popularization of numerical simulation techniques through computational fluid dy-namics (CFD) has led to the analysis of physical phenomena at new levels. The use ofthese techniques brought an increase of the speed of results and reduced costs related toexperiments. The application of CFD programs for thermal analysis is not widespread,especially when it comes to opensource software such as OpenFOAM. Thus, the objective ofthe present study is to model and simulate thermal analysis, with emphasis on thermogravi-metric analysis (TGA), using CFD with OpenFOAM, through biomassGasificationFoamsolver. For that, experimental data available in the literature were used for validate thesimulation. The importance of the magnitude of the sample density is analyzed by Biotnumber and numerical parameters, such as spatial and temporal convergence (Courantnumber), are also discussed in this work. The results obtained were satisfactory whencompared to TGA experiments for oil shale. Biot number demonstrated that the parametersof the experiment should be carefully selected so as to avoid possible deviations in theresults